2013
DOI: 10.1371/journal.pone.0079785
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Gadolinium-Enhanced MRI of Cartilage (dGEMRIC) Shows No Change in Cartilage Structural Composition after Viscosupplementation in Patients with Early-Stage Knee Osteoarthritis

Abstract: IntroductionViscosupplementation with hyaluronic acid (HA) of osteoarthritic (OA) knee joints has a well-established positive effect on clinical symptoms. This effect, however, is only temporary and the working mechanism of HA injections is not clear. It was suggested that HA might have disease modifying properties because of its beneficial effect on cartilage sulphated glycosaminoglycan (sGAG) content. Delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) is a highly reproducible, non-invasive surrogate meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 58 publications
(73 reference statements)
3
27
0
Order By: Relevance
“…HA-mediated chondroprotection has been demonstrated in animal, in vitro and clinical studies,56 including a recent article57 that found a decreased rate of medial and lateral tibial articular cartilage degeneration following HA injections through the use of a state-of-the-art, MRI-based assessment of cartilage integrity. Other studies of the structural impact of HA injections of similar design have, however, failed to demonstrate structural benefit to cartilage from one series of injections 58. Thus, for patients with knee OA, HA injections may offer benefits that extend beyond the issues of the statistical significance and clinical relevance of the symptomatic results that they eventuate.…”
Section: Discussionmentioning
confidence: 99%
“…HA-mediated chondroprotection has been demonstrated in animal, in vitro and clinical studies,56 including a recent article57 that found a decreased rate of medial and lateral tibial articular cartilage degeneration following HA injections through the use of a state-of-the-art, MRI-based assessment of cartilage integrity. Other studies of the structural impact of HA injections of similar design have, however, failed to demonstrate structural benefit to cartilage from one series of injections 58. Thus, for patients with knee OA, HA injections may offer benefits that extend beyond the issues of the statistical significance and clinical relevance of the symptomatic results that they eventuate.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 111 obese adults, dGEMRIC showed that weight loss over the course of a year resulted in increased cartilage proteoglycan content 106 . A recently published study evaluated articular cartilage using dGEMRIC after viscosupplementation with hyaluronic acid in patients with early knee OA 107 . The study found no change in the structural composition of cartilage after 14 weeks, even though symptomatic improvement was reported.…”
Section: Delayed Gadolinium-enhanced Mri Of Cartilage (Dgemric)mentioning
confidence: 99%
“…Van Tiel described and used a promising reproducible methodology based on this technique to explore the potentially structural effect of HA in early stage knee OA, unsuccessfully [40].…”
Section: Research Articlementioning
confidence: 99%